VD_FINDINFO HC / 2017 / 1083 vom 24. November 2017 - VD Tribunal cantonal (2017)
DROIT D'OBTENIR UNE DÉCISION, RETARD INJUSTIFIÉ, MESURE PROVISIONNELLE | 265 al. 2 CPC (CH), 319 let. c CPC (CH), 321 al. 4 CPC (CH)